Broadband and civic engagement in rural areas: What matters?. Issue 5 (19th October 2016) - Whitacre, Brian E.; Manlove, Jacob L.
Abstract: This article uses recent data on both broadband and civic engagement to assess how various aspects of broadband access might be related to community involvement in rural areas of the US. In particular, it seeks to answer whether broadband access, adoption, or infrastructure (as measured by community anchor institutions) has the strongest relationship with specific civic engagement metrics. The data include 19 specific civic engagement metrics from the 2011 Current Population Survey and 2011 data on broadband access and adoption from the National Broadband Map and the Federal Communications Commission. Scatterplots and regression analysis using both aggregate (state-level) data and individual (household-level) data were used to assess overall relationships. The results of both univariate and multivariate analyses suggest that it is the adoption of broadband that is the most influential to civic engagement overall; however, community anchor institutions are important for certain metrics such as interactions with neighbors or confidence in local schools.